Perceptions and Attitudes to a Terrorist Shock: Evidence from the UK - Carlos Bozzoli; Cathérine Müller (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
The emergence of transnational terrorism in Western countries has raised the debate about security measures, some of which could constrain civil liberties. This is the first paper that uses terrorist attacks (on 7th July, 2005 in London) as an exogenous source of variation to study the dynamics of risk perceptions and its impact on the readiness to trade off civil liberties for enhanced security. In this framework we show that the willingness to trade off security for liberties is dramatically affected by changes in individual risk assessments brought on after a terrorist attack, and document the extent of its persistence.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330; terrorism; civil liberties; risk perception